Nutrição mineral de hortaliças VII : absorção de nutrientes pela cultura da cebola - Haag, H.P.; Home, P.; Kimoto, T. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1970)
Onion plants (Allium cepa L. var. Baia Piriforme Precoce Piracicaba), 70 days, old were grown in pots containing 7 kg of quartz sand. Twice a day they were irrigated by percolation with complete solution. Every 15 days from the 70 th day plants were harvested divided into aerial part and bulb. The parts were weighed and analysed for N, P, K, Ca, Mg and S. Data obtained allowed for the following main conclusion: a) The initial rate of growth of the onion during the first 85 days is rather slow b) The uptake of nutrients is small until the 85 days, increasing at the 145 days. c) The following amounts of nutrients in kg/ha were absorved by a population of 166,666 plants with a production of 36,700 kg of onion: N 132.8 P 21.9 K 177.0 Ca 15.9 Mg 17.8 S 33.8